Autekologi Damar Asam Shorea hopeifolia (F. Heim) Symington di Taman Nasional Bukit Barisan Selatan, Lampung - Marfuah Wardani; Nur M. Heriyanto (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumberdaya Genetik Pertanian, 2015)
Autecological research of Shorea hopeifolia (F. Heim) Symington was done at Resort Pemerihan, National Park of South Bukit Barisan, Lampung in November 2014. The data was collected using a square plot of 20 m x 20 m, number of sample units made was three plots and each plot was made to four subplots with the distance of 50 m between the subplots, distance between the plots was 2,000 m. The results showed that S. hopeifolia was found at altitudes above 260 m asl, alongside of the hill with a rather steep topography and groups. Vegetation encountered in the surrounding consisted of Dipterocarpus kunstleri King. with IVI of 28.89%, Shorea ovalis Blume with IVI of 18.83% and Lithocarpus elegans Blume with IVI of 15.06%. The physical environment temperature was between 25–35°C, humidity was between 52–76%, slope was between 15–65%, and altitude from sea level was between 276 to 350 m. D. kunstleri King. associated with the most powerful S. hopeifolia (close to 1) Ochiai index of 0.81, followed by S. ovalis Blume Ochiai index of 0.65 and Dillenia excelsa (Jack) Gilg. Ochiai index 0.52. Natural regeneration was assisted by wildlife especially hornbill (Buceros rhinoceros) and the flow of rain water. AbstrakPenelitian autekologi damar asam (Shorea hopeifolia (F. Heim) Symington) telah dilakukan di Resort Pemerihan, Taman Nasional Bukit Barisan Selatan, Lampung pada bulan November 2014. Pengumpulan data menggunakan plot bujur sangkar ukuran 20 m x 20 m, jumlah satuan contoh yang dibuat tiga plot dan masing-masing plot dibuat 4 subplot dengan jarak antarsubplot 50 m, jarak antarplot 2.000 m. Hasil penelitian menunjukkan bahwa damar asam dijumpai pada ketinggian tempat di atas 260 m dpl, di pinggir bukit dengan topografi agak curam dan berkelompok. Vegetasi di sekitarnya yang dijumpai adalah kruing (Dipterocarpus kunstleri King.) dengan INP sebesar 28,89%, meranti merah (Shorea ovalis Blume) INP = 18,83%, dan Lithocarpus elegans Blume dengan INP = 15,06%. Lingkungan fisik suhu antara 25–35°C, kelembaban udara antara 52–76%, kemiringan lahan antara 15–65% dan ketinggian tempat dari permukaan laut antara 276 sampai 350 m. Jenis kruing (D. kunstleri King.) berasosiasi dengan damar asam paling kuat (mendekati 1) indeks Ochiai 0,81 diikuti meranti merah (S. ovalis Blume) indeks Ochiai 0,65 dan sempur Dillenia excelsa (Jack) Gilg. indeks Ochiai 0,52. Regenerasi alami dibantu oleh satwa liar terutama burung rangkong (Buceros rhinoceros) dan aliran air hujan.